Rendimiento y calidad en la tranformación de madera rolliza (troza) a madera aserrada de la especie Pterocarpus rohrii Vahl (palisangre) en el aserradero Consorcio Forestal Loreto S.A.C Iquitos - Loreto -2022 - Vasquez Macedo, Maria Isabel (2022)
This study was carried out at the wood processing plant of the Consorcio Forestal Loreto S.A.C sawmill, owned by the engineer William Castro located on the Iquitos-Nauta Km 4 highway, in order to determine the yield of Perocarpus rohrii vahl (palisangre) in the sawmill Consorcio Forestal Loreto S.A.C. From the results obtained, it is found that the yield coefficient for the species base don the gross volumen was 0.73%. The yield coefficient for the species as a function of sawn volumen was 0.82% for commercial longwood, 0.12% for narrow longwood, 0.027% for shortwood, and 0.034% for strips. According to the clasificación of the Wood with the NHLA standars, 58% of Fas and Selecta Quality was obtained, 25% of common quality Nº.1, 13% of common quality Nº.2 and 4% of Wood for the national market. According to the classification standards of the national market, 27.04% of first quality, 25.97% of second quality, 25.67% of third quality and 21.33% of Wood for the national market were obtained. The sale Price of the total lot of wood calculated for the national marked was s/. 126,621.60, while the sale Price of the same lot for the export market was s/. 289,126.89.